2007
DOI: 10.1017/s0007114507746871
|View full text |Cite
|
Sign up to set email alerts
|

Dietary soya intake alters plasma antioxidant status and lipid peroxidation in postmenopausal women with the metabolic syndrome

Abstract: Postmenopausal women with the metabolic syndrome are at high risk of oxidative stress. Several studies have suggested possible antioxidant properties of soya, but little evidence is available regarding the effect of soya on oxidative stress in postmenopausal women with the metabolic syndrome. The objective of the present study was to determine the effects of soya consumption on plasma total antioxidant capacity (TAC) and malondialdehyde (MDA) level in postmenopausal women with the metabolic syndrome. A randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 53 publications
(62 reference statements)
4
36
0
1
Order By: Relevance
“…Because isoflavones may influence BP [59], several studies on soy could not be taken into account because observational data were not adjusted for isoflavone intake [60][64], or because, in trials, soy protein contained isoflavones [65][69]. To the best of our knowledge, there are at present no other studies on specific protein sources and BP.…”
Section: Resultsmentioning
confidence: 99%
“…Because isoflavones may influence BP [59], several studies on soy could not be taken into account because observational data were not adjusted for isoflavone intake [60][64], or because, in trials, soy protein contained isoflavones [65][69]. To the best of our knowledge, there are at present no other studies on specific protein sources and BP.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that other soy products such as soy nut might have more beneficial effects on cardiovascular risks (7), inflammatory markers (8), and oxidative stress (27) than textured soy protein. Further studies are required to assess the effects of soy nut among type 2 diabetic patients with nephropathy.…”
Section: Methodsmentioning
confidence: 99%
“…Frequent consumption of legumes, as part of a healthy diet, has been inversely associated with CVD (Bazzano et al, 2001;Flight & Clifton, 2006). Human studies have shown that legume consumption attenuate oxidative stress, improves serum antioxidant capacity and reduces serum concentration of total and low-density lipoprotein-cholesterol, triglycerides, adhesion molecules and inflammatory biomarkers, all of which are risk factors for the development of CVD (Azadbakht et al, 2007;Crujeiras, Parra, Abete, & Martinez, 2007;Esmaillzadeh & Azadbakht, 2012;Taku et al, 2007). These protective effects of legumes against CVD have been related to their nutritional composition (Campos-Vega, Loarca-Piña, & Oomah, 2010).…”
Section: Introductionmentioning
confidence: 99%